Metal-mediated alkynediol cycloisomerization: first and second generation formal total syntheses of didemniserinolipid B - Das, Shyamsundar; Induvadana, Boddeti; Ramana, C. V. (Tetrahedron, 2013)
A formal total synthesis of didemniserinolipid B was developed by employing a regioselective metal-mediated 6-endo-dig alkynol-cycloisomerization reaction. Two routes for the synthesis of key Burke's intermediate have been developed. Our initial approach involved the introduction of a C-17-allcynol followed by Pd-mediated cycloisomerization and then coupling with the serinol unit prior to the introduction of an alpha,beta-unsaturated ester unit through selective oxidation of 1 degrees-OH followed by a two-carbon Wittig homologation. Alternatively, the second generation strategy featuring the serinol coupling with the C-17-alkynol followed by alkyne addition to the epoxide and subsequent Au-mediated cycloisomerization of an acetonide protected alkynediol unit has been executed. This approach has avoided several late stage protection-deprotection events. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Alkynol-cycloisomerization; Bicyclic ketal; Gold catalysis; Palladium catalysis; Zipper reaction

Formal total synthesis of (-)-kumausallene - Das, Shyamsundar; Ramana, Chepuri V. (Tetrahedron, 2015)
Deacetylkumausyne-a penultimate intermediate in Tang's total synthesis of (-)-kumausallene has been synthesized employing a chiral pool approach and thus culminating in a formal total synthesis of kumausallene. The opening of an epoxide with alkyne (use of Birch reduction for the selective construction of E-pent-3-enyl group) and C-allylation have been used to introduce the pendant alkenyl side chains. Initial attempts to execute an alternative to Tang's route comprising a prior installation of the bromoallene unit via bromoetherification and subsequent S(N)2 displacement are unsuccessful. To overcome this, an alternative approach was developed to arrive at Deacetylkumausyne (another natural product that has been synthesized and characterized by Tang's group). Thus, this overall exercise has culminated in a formal total synthesis of (-)-kumausallene. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Bis-THF natural products; Chiral pool; Deacetylkumausyne; Total synthesis; Wittig reaction

Simple method for the preparation of ultra-small palladium nanoparticles and their utilization for the hydrogenation of terminal alkyne groups to alkanes - Seth, Jhumur; Kona, Chandrababu Naidu; Das, Shyamsundar; Bhagavatula L. V. Prasad (Nanoscale, 2015)
A simple and convenient method for the preparation of ultra-small palladium nanoparticles (Pd-NPs) by a modified digestive ripening method is described. These nanoparticles catalyse the hydrogenation of the terminal alkyne groups to alkanes selectively, and show no effect on other labile protecting and internal alkyne or internal/external alkene groups present in the molecule.

Total synthesis of notoryne - Senapati, Sibadatta; Das, Shyamsundar; Ramana, Chepuri V. (Journal of Organic Chemistry, 2018)
The structure of notoryne comprises a halogenated 2,2'-bifuranyl moiety along with a terminal cis-enyne unit. In this work, we document the first total synthesis of notoryne, confirming its assigned relative and absolute configurations. The devised route comprises a glucose diacetonide-derived chiral pool intermediate as the starting point and 5-endo bromo-etherification for making the key bis-furan unit, anomeric C-allylation, as well as a relay cross-metathesis to install the cis-enyne unit.

Synthesis of four diastereomers of notoryne and their C-13 NMR chemical shifts analysis - Senapati, Sibadatta; Das, Shyamsundar; Dixit, Ruchi; Vanka, Kumar; Ramana, V, Chepuri (Journal of Chemical Sciences, 2021)
In this manuscript we document the details of the synthesis of four diastereomers of notoryne. The synthesis of one of the diastereomer having a similar relative stereochemistry of substituents on the both THF rings like notoryne, however, being the relative stereochemistry between the bridging carbon of these two THF units is changed from anti to syn has been executed mainly to learn how the ring carbon chemical shifts vary with this change. Interestingly, the deviations are found mainly for the carbons of THF ring that bears the Br-group. In addition to this isomer, three more diastereomers having the relative stereochemistry of substituents on either of the THF rings varied have been also synthesized. All four diastereomers have been subjected for extensive NMR studies and their C-13 NMR chemical shifts have been compared with notoryne and laurendecumenyne B. In addition, chemical shifts for the four diastereomers along with these natural products were calculated with the help of DFT calculations and compared to the experimentally obtained chemical shift values.